2016
DOI: 10.1016/j.toxrep.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 receptor agonist exenatide restores atypical antipsychotic clozapine treatment-associated glucose dysregulation and damage of pancreatic islet beta cells in mice

Abstract: Background and aimsThe aim of this study was to investigate the effect of a glucagon-like peptide-1 receptor agonist (GLP-1RA), exenatide, on clozapine-associated glucose dysregulation in mice.Materials and methodsWe randomly separated B6 male mice into four groups (A to D). Mice in groups C and D received a daily oral dose of 13.5 mg/kg body weight of clozapine for 4 months. Mice in groups B and D received 1 μg of exenatide daily. The body weight and blood glucose before and 2 h after clozapine treatment were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The higher glucose levels in the FEP AP2 subgroup may be indicative of a sub-clinical oxidative stress response of the pancreatic cells, also related to the reduced adherence to the MedDiet. In a study of Hsu et al, clozapine categorized here in the AP2, was associated with glucose dysregulation in a mouse model [ 33 ]. In FEP treated with AP2, MedDiet appeared to be beneficial in regulating glucose levels [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The higher glucose levels in the FEP AP2 subgroup may be indicative of a sub-clinical oxidative stress response of the pancreatic cells, also related to the reduced adherence to the MedDiet. In a study of Hsu et al, clozapine categorized here in the AP2, was associated with glucose dysregulation in a mouse model [ 33 ]. In FEP treated with AP2, MedDiet appeared to be beneficial in regulating glucose levels [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This increase in glucagon levels can directly increase HGO, as mentioned previously. In this line, it was reported that the GLP-1 receptor agonist exenatide reversed the damage to pancreatic islets in male C57BL/6 mice treated for 4 months with clozapine (13.5 mg/kg, orally), suggesting a dysregulation of GLP-1-mediated signaling and the subsequent impairment of pancreatic hormone secretion [147]. An increase in glucagon levels after clozapine treatment (5 mg/kg, i.v.)…”
Section: New Insights Into the Molecular Mechanisms By Which Sgas mentioning
confidence: 99%
“…For example, the rs10423928 polymorphism (A/T) in the β-cell glucose-dependent insulinotropic polypeptide receptor ( GIPR ), which stimulates insulin secretion upon binding of the incretin GIP, was associated with increased insulin levels in an oral glucose tolerance test in patients with schizophrenia treated with olanzapine [158]. As discussed earlier, long-term treatment with high-risk diabetogenic SGAs has been also linked to decreased GLP-1 levels in rats [146], and the positive effects of GLP-1 analogs have been proved in animals [147] and humans [159,160]. Correspondingly, GCG (encoding for a preprotein cleaved into four different proteins, including GLP-1 and glucagon) and GLP1R have been assessed as potential pharmacogenetic markers of antipsychotic response.…”
Section: New Insights Into the Molecular Mechanisms By Which Sgas mentioning
confidence: 99%
“…The majority of rodent studies demonstrated evidence of apoptosis (e.g., increased terminal deoxynucleotide transferase dUTP nick-end labeling staining or caspase-3 activation) between weeks 1 and 4 of treatment (Wasti et al, 2006;Jarskog et al, 2007;Huang et al, 2012;Jia et al, 2014;Zlatkovi c et al, 2014;Hsu and Fu, 2016;Khalaf et al, 2019) using doses that would approximate therapeutic concentrations in patients (Lobach and Uetrecht, 2014a). One study also noted that clozapine induced autophagy within hours of administration (Kim et al, 2018), and others noted decreased proliferation within the first few weeks of treatment (Huang et al, 2012;Hsu and Fu, 2016;Khalaf et al, 2019) as well. Translocation of apoptosis-inducing factor was not observed in the striatum of clozapine-treated patients or in rodents after 1 month of treatment (Skoblenick et al, 2006), suggesting against the involvement of caspase-independent cell death with clozapine.…”
Section: Clozapinementioning
confidence: 99%